2023
DOI: 10.3390/curroncol30040331
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review Assessing the Impact of Vitamin D Levels on Adult Patients with Lymphoid Malignancies

Abstract: Vitamin D deficiency has been correlated with various conditions, including the risk of developing lymphoid malignancies. This systematic review aimed to assess the association between vitamin D levels at diagnosis of lymphoid malignancies, patient outcomes, and survival. A systematic review was conducted, encompassing 15 studies published until January 2023, involving 4503 patients, examining the relationship between vitamin D and lymphoid cancers. The median age of the patients was 56.5 years, with a median … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Some research suggests that vitamin D supplements can improve the efficiency of therapy, particularly chemosensitivity and drug response. However, some investigations, such as that by Kelly et al, found no significant correlation between deficiency of VD and the reasons for mortality, or survival outcomes ( Potre et al, 2023 ). There are controversial points in the literature regarding the role of vitamin D and vitamin D receptor gene variation in terms of any associated increased risk of developing cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some research suggests that vitamin D supplements can improve the efficiency of therapy, particularly chemosensitivity and drug response. However, some investigations, such as that by Kelly et al, found no significant correlation between deficiency of VD and the reasons for mortality, or survival outcomes ( Potre et al, 2023 ). There are controversial points in the literature regarding the role of vitamin D and vitamin D receptor gene variation in terms of any associated increased risk of developing cancer.…”
Section: Discussionmentioning
confidence: 99%
“…VD is a prohormone substance necessary for various different biological functions in the body such as calcium homeostasis, immunological regulation, and cell proliferation ( Potre et al, 2023 ). It also plays a role in reducing lymphocyte and other human-derived malignancy cell proliferations and differentiations.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D, an essential fat-soluble vitamin, plays a pivotal role in maintaining various aspects of health, including calcium balance, bone health, and immune system modulation. There is growing interest in exploring its potential benefits in managing UFs due to the presence of vitamin D receptors in uterine tissue and associations between vitamin D deficiency and gynecological conditions like UFs [ 68 ]. Vitamin D supplementation, available in oral or injectable forms, is commonly recommended to address deficiencies and promote overall well-being.…”
Section: Optimal Dietary Choices To Consider (Food Modifications)mentioning
confidence: 99%
“…Vitamin D is an essential fat-soluble vitamin that plays a crucial role in various aspects of health, including maintaining calcium balance, supporting bone health, and modulating the immune system [44,45]. The presence of VDR in uterine tissue and the observed associations between vitamin D deficiency and various gynecological conditions, including UFs, have sparked interest in investigating the potential benefits of vitamin D in the management of UFs [46][47][48][49].…”
Section: Vitamin D Serum Level Checkup and Proper Supplementationmentioning
confidence: 99%